(untitled) (Observatorio Económico, 2014)
For Zygmunt Bauman, consumption is “an essential function for biological survival, whose roots are as old as life itself.” At some point in history, however, a breaking point occurred when consumption became “consumerism.” That is, it became the main purpose of people’s existence, the driving force of society, and an economy of excess, waste, and deception that relies on irrationality and emotion, in which people themselves become consumer goods. Continue reading...